Removal and Preconcentration of Pb(II), Cr(III), Cr(VI) from the Aqueous Solution and Speciation of Cr(III)-Cr(VI) by Using Functionalized Amberlite XAD-16 Resin with Dithioethylenediamine - Dolak, Ibrahim; Tegin, Ibrahim; Guzel, Remziye; Ziyadanogullari, Recep (Asian Journal of Chemistry, 2010)
Amberlit XAD-16 was functionalized using dithioethylenediamine as a ligand and characterized by elemental analysis and FTIR spectroscopy. The effects of contact time, pH, electrolyte and the concentration of eluent on separation and preconcentration of Pb(II), Cr(III) and Cr(VI) were studied. In addition, the batch capacity for each ion was determined under the optimum conditions. The preconcentration yields of Pb(II), Cr(III) and Cr(VI) were found to be 96.60 ± 3.02, 102.20 ± 3.00 and 100.64 ± 2.24 %, respectively, with 500 times preconcentration factor under the optimum conditions. The speciation of Cr(III)-Cr(VI) was studied, it was determined that Cr(III) separated in 93.24 ± 2.21 % yield from the solution containing Cr(III)-Cr(VI) by using Amberlit XAD-16-dithioethylenediamine and Cr(VI) remained in the solution at pH 4, while Cr(VI) separated in 101.43 ± 3.09 % yield from the solution containing Cr(III)-Cr(VI) and Cr(III) remained in the solution at pH 7.50 by using Amberlit XAD-16-dithioethylenediamine- Pb(II).